Characterization of scaffold carriers for BMP9‐transduced osteoblastic progenitor cells in bone regeneration. Issue 10 (29th October 2013) - Shui, Wei; Zhang, Wenwen; Yin, Liangjun; Nan, Guoxin; Liao, Zhan; Zhang, Hongmei; Wang, Ning; Wu, Ningning; Chen, Xian; Wen, Sheng; He, Yunfeng; Deng, Fang; et al.
Abstract Successful bone tissue engineering at least requires sufficient osteoblast progenitors, efficient osteoinductive factors, and biocompatible scaffolding materials. We have demonstrated that BMP9 is one of the most potent factors in inducing osteogenic differentiation of mesenchymal progenitors. To facilitate the potential use of cell‐based BMP9 gene therapy for bone regeneration, we characterize the in vivo osteoconductive activities and bone regeneration potential of three clinically used scaffold materials, type I collagen sponge, hydroxyapatite‐tricalcium phosphate (HA‐TCP), and demineralized bone matrix (DBM), using BMP9‐expressing C2C12 osteoblastic progenitor cells. We find that recombinant adenovirus‐mediated BMP9 expression effectively induces osteogenic differentiation in C2C12 cells. Although direct subcutaneous injection of BMP9‐transduced C2C12 cells forms ectopic bony masses, subcutaneous implantation of BMP9‐expressing C2C12 cells with collagen sponge or HA‐TCP scaffold yields the most robust and mature cancellous bone formation, whereas the DBM carrier group forms no or minimal bone masses. Our results suggest that collagen sponge and HA‐TCP scaffold carriers may provide more cell‐friendly environment to support the survival, propagation, and ultimately differentiation of BMP9‐expressing progenitor cells. This line of investigation should provide important experimental evidence for further preclinical studies in BMP9‐mediated cell‐based approach to bone tissue engineering. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3429–3438, 2014.